Shorland, The Lost Queen (Atlantic Books, 2024) - Chelsea Reutcke (Royal Studies Journal)
Review of Sophie Shorland, The Lost Queen: The Surprising Life of Catherine of Braganza, Britain’s Forgotten Monarch (London: Atlantic Books, 2024).